Parasocial relationship as a form of individualism in the global era in Gail Honeyman’s novel Eleanor Oliphant Is Completely Fine - Andini Damayanti; Rahayu Puji Haryanti (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
In the context of today’s global media culture, Gail Honeyman’s Eleanor Oliphant Is Completely Fine portrays how individuals develop emotional attachment to mediated figures, as the main character forms a parasocial relationship with a musician. Although not fully explained in the narrative, this reflects a common phenomenon in the global era. This research aims to investigate the connection between mediated intimacy and the global era, as well as its impact on the development of individualism. Employing a descriptive qualitative method and drawing on Jean Baudrillard’s theory of hyperreality, this research also explains how reality has been replaced by simulation via the media. The analysis reveals that the main character forms an emotional attachment based on media representations rather than fundamental interactions, symbolizing the shifting meaning of reality in modern life. Such attachment encourages the main character to withdraw from social situations and to prefer to live in an imaginary world. This reflects the rise of individualism in a global society influenced by the media. Beyond previous studies that primarily emphasize the psychological dimensions of parasocial ties, this research contributes by highlighting their cultural implications and significance in understanding contemporary social dynamics.